Political connectedness and formal finance in transition economies - Kobil Ruziev (IZA World of Labor, 2017)
Although small- and medium-sized enterprises (SMEs) represent more than 90% of all enterprises and play an important role in employment generation, they lack access to affordable formal finance. Conventionally, market failures and information imperfections are seen as majorcauses of this misallocation. However, the role of social and political factors in resource allocation, including access to formal finance, has recently become more widely accepted. Firm-level evidence from post-communist economies, for example, shows that political connectedness improves access to bank credit, but is not associated with enterprise growth.
Keywords: G38; P2; 330; transition economies; formal finance; connectedness; firm-level analysis